Essential Oil Extraction of Fennel Seed (Foeniculum vulgare) Using Steam Distillation - Astrilia Damayanti; Eko Setyawan (Chemical Engineering Diponegoro University, 2012)
Indonesia is a potential country in developing essential oils which is each part of the plants produce essential oils such as leaf, seed, fruit, and root. One of the potential plants is fennel. Fennel oil distillation used fennel seed from Cepogo District, Boyolali Regency. The characteristics of the seed are; the color is black and the length is 0,2 centimeters. The condition operation to exctract of the fennel seed are 1 atm and 7,5 hours. The calculation of the time started when the first fennel oil dropped into the decanter. It finished when the fennel oil was not dropped anymore. The color is bright and muddy. The last process is add 1% (m/m) Na2SO4 anhidrous into fennel oil to absorp remain water in it. The distillation process produce fennel oil102,125 grams. Sample of fennel oil tested which are density test, solubility on 90% alcohol, GC-MS test, and AAS test. The result shows that fennel oil from the fennel seed is 2,0425%. The tested samples contain the brightest and the muddies sample. The density of 0,9500 and 0,949 g/cc respectively that is not fulfill to the Food Chemical Codex (FCC). Samples solubility in 90% alcohol (1:3) is fulfill to the the Food Chemical Codex (FCC). Three main components of the brightest sample are anethole (47,51%), estragole (22,41%), and α-fensone (21,92%) while the muddiest sample’s components are anethole (52,38%), estragole (21,37%),and α-fensone (15,74%). The AAS test shows that fennel oil contains 65,1473 ppm which does not fulfill the Indonesian National Standards of patchouli and clove leaf oil. [Keywords— essential oil; extraction; fennel seed; steam distillation